A NEW BOVID, ASOLETRAGUS GENTRYI GEN. N. ET N. SP., FROM MONTE TUTTAVISTA (OROSEI, EASTERN SARDINIA, ITALY) (Rivista italiana di Paleontologia e Stratigrafia, 2006)
This work describes a new bovid, Asoletragus gentryi n. gen. et sp., from the late Pliocene/early Pleistocene fossiliferous fissure fillings (Cava VI,3) in the karst network at  Monte Tuttavista (Sardinia, Italy). It differs from other genera in its straight, almost conical, horn-cores, which diverge slightly from the sagittal plane, are very close together at their bases and slant strongly backwards (nearly parallel to the glenoid surface of the temporal bone). The very peculiar shape and position of these horn-cores render their phylogenetic relationship with other taxa from the Miocene of Europe and other circum-Mediterranean countries uncertain. Given the global features of the horn-cores and the absence of any alcelaphine-like tooth in the Monte Tuttavista samples, the hypothesis that Asoletragus belongs to an archaic "Caprinae" cannot be ruled out, despite the presence of quite a large frontal sinus rising through the pedicel and at least one-third of the horn-core proper. Pending the discovery of other fossils from this taxon, one may only hypothesize regarding its phylogeny. SHORT NOTE